2022
DOI: 10.3390/molecules27238366
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activity of Pumpkin Byproducts: Antimicrobial and Antioxidant Properties

Abstract: Pumpkin fruits are widely appreciated and consumed worldwide. In addition to their balanced nutritional profile, pumpkin species also present valuable bioactive compounds that confer biological and pharmacological properties to them. However, the seeds, peels, and fibrous strands resulting from pumpkin processing are still poorly explored by the food industry. The current study used those fruit components from the genotypes of pumpkin that are economically significant in Portugal and Algeria to produce bioacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
19
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 38 publications
9
19
0
Order By: Relevance
“…P3 was the sample presenting the lowest antioxidant potential, in accordance with its lower phenolic compounds content. The IC 50 values obtained in the present study were comparable or better than those reported for Portuguese and Algerian pumpkins [ 3 ], which presented IC 50 values ranging from 88 to 209 µg/mL and 335 to 588 µg/mL for the OxHLIA assay and from 3921 to 7765 µg/mL and 2123 and 4569 µg/mL for the TBARS assay, respectively. These findings indicate the high antioxidant capacity of pumpkin fruit waste and highlight the potential of its further valorization in the food industry, since a significant correlation between the polyphenol extraction efficiency and the antiradical potential of the extracts has been well-confirmed [ 28 ].…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…P3 was the sample presenting the lowest antioxidant potential, in accordance with its lower phenolic compounds content. The IC 50 values obtained in the present study were comparable or better than those reported for Portuguese and Algerian pumpkins [ 3 ], which presented IC 50 values ranging from 88 to 209 µg/mL and 335 to 588 µg/mL for the OxHLIA assay and from 3921 to 7765 µg/mL and 2123 and 4569 µg/mL for the TBARS assay, respectively. These findings indicate the high antioxidant capacity of pumpkin fruit waste and highlight the potential of its further valorization in the food industry, since a significant correlation between the polyphenol extraction efficiency and the antiradical potential of the extracts has been well-confirmed [ 28 ].…”
Section: Resultssupporting
confidence: 82%
“…(-)-Epicatechin (peak 1) was the least representative compound in samples P1 and P2, contrarily to the results reported for the Portuguese pumpkin extracts, in which this was the most abundant compound [ 3 ]. The extracts from P1 and P2 showed higher contents of total phenolic compounds, approximately 3 mg/g each, while P3 presented almost half of the total concentration found in P1.…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations